Extraction of Brain Tumour in MRI Images using Marker Controlled Watershed Transform Technique in MATLAB - Maheshwari, Danyal; Shah, Ali Akber; Shaikh, Muhammad Zakir; Chowdhry, Bhawani Shankar; Memon, Sara Rahman (British Journal of Healthcare and Medical Research, 2015)
In recent years, substantial research has been carried out in the field of image processing to evaluate different structures and information from images. Image processing techniques have played a pivotal role in a wide range of medical image applications. They have been widely used to design different computational algorithms for extracting clinical information from medical images in different modalities including MRI, CT and Ultrasound. This paper aims to propose the use of image processing techniques in the medical ﬁeld. The objective of this paper is to develop a MATLAB based algorithm that can be used to extract a brain tumor from a MRI Image. In this research, we have performed some noise removal functions, segmentation techniques and morphological operations for detection and extraction which are the basic concepts of image processing. We have developed a Watershed Transform technique based on internal and external markers. The detection and extraction of tumor from MRI image of the brain is done by using MATLAB software.